Franco Aixelá, J., & Olalla-Soler, C. (Eds.). (2022). 50 Years Later. What Have We Learnt after Holmes (1972) and Where Are We Now?. Las Palmas de Gran Canarias: Universidad de Las Palmas de Gran Canaria, Servicio de Publicaciones y Difusión Científica. https://doi.org/10.20420/1699.2022.646 (pp.190) - Wang, Yanmeng; Zhu, Zhiqiang (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2024)
/